Pengaruh Penerapan Video Pembelajaran Pada Mata Pelajaran Pengetahuan Bahan Tekstil Terhadap Hasil Belajar Siswa Kelas X Tata Busana SMK Sunan Drajat - Adillah Mahasin Thuba; Urip Wahyuningsih; Yuhri Inang Prihatina; Imami Arum Tri Rahayu (Journal on Education, 2023)
This study was a pre-experimental design type of one-group pre-test post-test design. The research design was carried out in a single group, only in one class, there was no control class, so there was no comparison for measurements. The purpose of this study was to determine the learning outcomes of class X fashion design at SMK Sunan Drajat before and after the application of instructional video media, to determine the effect of applying learning videos on student learning outcomes for class X fashion design at SMK Sunan Drajat. Data collection techniques through cognitive and psychomotor tests. The data analysis method used is the average formula and t-test. The results of the study, (1) Obtained a pre-test average of 47.81 and a post-test average of 87.27. Then the results of the post-test scores increased by 39.46. (2) Based on the calculation results of the t-test, it shows results with a Sig. (2-tailed) of 0.000<0.05. Thus T-count = 43.276 > T-table = 2.060 this means that Ho is rejected and Ha is accepted. which means there is a significant influence on student learning outcomes in the subject of knowledge of textile materials for class X Fashion Design at SMK Sunan Drajat.